Aktivitas Antibakteri Ekstrak Metanol Buah Ketapang (Terminalia catappa Linn.) Terhadap Pertumbuhan Staphylococcus epidermidis Dan Salmonella typhi - Masnur Turnip, Dominika Istarina, Siti Khotimah, (Universitas Tanjungpura, 2015)
The most commonly found disease causing microorganisms are the Staphylococcus epidermidis and Salmonella tyhpi bacteria. These bacteria can be controlled by using natural antibacterial ingredients, one of which is the fruit of ketapang (T. catappa). This research aimed to find out the antibacterial intensity of methanol extract of the T. catappa fruit in inhibiting the growth of S. epidermidis and S. typhi. This research used the disc diffusion method. The extract was given treatments with 25%, 50% and 75%, both positive and negative control treatments. Each treatment was inoculated with a bacterial suspension, and then the filter paper that had been soaked in the extract was aseptically placed on the surface of the media, incubated with a temperature of 370C for 24 and 48 hours, then the area of clear zone around the filter paper was observed and meassured. The research findings showed that the fruit of T. catappa had an inhibitory effect against both bacteria tested. The extract of the fruit of T. catappa at the concentration of 50% was found to be the optimum concentration for inhibiting S. epidermidis and S. typhi.